2012
DOI: 10.1007/s00376-011-0216-3
|View full text |Cite
|
Sign up to set email alerts
|

The East Pacific Wavetrain: Its variability and impact on the atmospheric circulation in the boreal winter

Abstract: The East Pacific wavetrain (EPW) refers to here the intense stationary wave activity detected in the troposphere over the East Pacific and North America in 45 northern winters from 1958 to 2002. The EPW is generated in the lower troposphere over the East Pacific, propagating predominantly eastward into North America and slightly upward then eventually into the stratosphere. The intensity of the EPW varies from year to year and exhibits apparent decadal variability. For the period 1958-1964, the EPW was in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…vectors turns slightly equator-ward. The largest west-east momentum fluxes over Siberia change the least, which is also supported by the diagnostics for the past decades in observations (Zhou et al, 2012). The strong semi-permanent pressure systems, such as the Siberia high and Aleutian low, stabilize the variability of the planetary wave activity's surroundings.…”
Section: Responses To Increasing Cosupporting
confidence: 63%
See 1 more Smart Citation
“…vectors turns slightly equator-ward. The largest west-east momentum fluxes over Siberia change the least, which is also supported by the diagnostics for the past decades in observations (Zhou et al, 2012). The strong semi-permanent pressure systems, such as the Siberia high and Aleutian low, stabilize the variability of the planetary wave activity's surroundings.…”
Section: Responses To Increasing Cosupporting
confidence: 63%
“…The vertical component of waves, also called wave heat fluxes, also decrease, varying from -8.1% to -28.6%, with the maximum decrease occurring over the Eastern North Pacific. The diagnostics for the past several dec-ades from the reanalysis data also support the conclusion that the vertical component of wave fluxes over the Eastern North Pacific has the largest sensitivity to climate change among the three centers (Zhou et al, 2012), which is partly attributed to the influences of the internal mode of the air-sea system from low latitudes, such as El Niño and the Southern Oscillation (ENSO) and the Pacific North America (PNA) teleconnection pattern.…”
Section: Responses To Increasing Cosupporting
confidence: 60%
“…[12] Next, we explore the relationship between the AL-IL seesaw, the EPWs, and the polar vortex. Zhou et al [2012] found that the AL and the EPWs are closely related. For a weak (strong) AL, the vertical component of the stationary wave activity flux over the eastern Pacific is weak (strong), and the associated EPW is also weak (strong).…”
Section: Resultsmentioning
confidence: 97%
“…Zhou et al . [] suggested that the EPWs and the PNA are the same phenomenon as revealed in different variables. The EPWs correspond to wave activity fluxes, while the PNA is in the form of a wave train of geopotential height anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…An issue remains to be further explored in the future is the possible factors for the change in the spatial structure of the winter AO. Studies have demonstrated that structure of the winter AO can be impacted by several factors, such as the solar cycle [46], polar vortex [47,48], the Aleutian Low-Aleutian Low oscillator [49], and the eastern Pacific atmospheric wave train [50,51]. Individual and combined roles of the above factors in modulating the spatial structure of the winter AO need to be investigated in the future.…”
Section: Summary and Discussionmentioning
confidence: 99%